Procoagulant Phosphatidylserine-Exposing Platelets in vitro and in vivo - Reddy, Emily C.; Rand, Margaret L. (Frontiers in Cardiovascular Medicine, 2020)
The physiological heterogeneity of platelets leads to diverse responses and the formation of discrete subpopulations upon platelet stimulation. Procoagulant platelets comprise one such subpopulation, a key characteristic of which is exposure of the anionic aminophospholipid phosphatidylserine (PS) on the activated platelet surface. PS exposure on a subpopulation of platelets facilitates assembly of the intrinsic tenase and prothrombinase complexes, thereby accelerating thrombin generation on the activated platelet surface, contributing importantly to the hemostatic process. This review focusses on mechanisms involved in platelet PS exposure, and accompanying events, induced by physiologically-relevant agonists, then contrasting these with PS exposure resulting from intrinsic pathway-mediated apoptosis in platelets. Pathologies of PS exposure, both inherited and acquired, are described. A consideration of platelet PS exposure as an antithrombotic target concludes the review.